2013
DOI: 10.1016/j.celrep.2013.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Phosphate Export by the Retrovirus Receptor XPR1 in Metazoans

Abstract: Inorganic phosphate uptake is a universal function accomplished by transporters that are present across the living world. In contrast, no phosphate exporter has ever been identified in metazoans. Here, we show that depletion of XPR1, a multipass membrane molecule initially identified as the cell-surface receptor for xenotropic and polytropic murine leukemia retroviruses (X- and P-MLV), induced a decrease in phosphate export and that reintroduction of various XPR1 proteins, from fruit fly to human, rescued this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
174
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(182 citation statements)
references
References 43 publications
8
174
0
Order By: Relevance
“…This is in accordance with the recent finding that the SPX domain of the mammalian PHO1 homolog XPR1 is also not required for Pi export (Giovannini et al, 2013;Wege and Poirier, 2014). However, expression of the SPXtruncated 4TMEXS protein was unable to complement the pho1 mutant and even strongly exacerbated the reduction in shoot growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the recent finding that the SPX domain of the mammalian PHO1 homolog XPR1 is also not required for Pi export (Giovannini et al, 2013;Wege and Poirier, 2014). However, expression of the SPXtruncated 4TMEXS protein was unable to complement the pho1 mutant and even strongly exacerbated the reduction in shoot growth.…”
Section: Discussionsupporting
confidence: 92%
“…The mammalian PHO1 homolog, named XPR1, was initially identified as a protein acting as a cell surface receptor for retroviruses (Battini et al, 1999;Yang et al, 1999). Heterologous expression of XPR1 either in Nicotiana benthamiana or in mammalian cultured cells showed that it also acts as a Pi exporter (Giovannini et al, 2013;Wege and Poirier, 2014). PHO1 proteins are composed of three distinct regions (Wang et al, 2004).…”
mentioning
confidence: 99%
“…The EXS domain, named after the yeast protein Erd1, human Xpr1 and yeast Syg1 (Pfam: PF03124), contains several predicted transmembrane helices [15] that likely form a channel for transferring phosphate. The association between the N-terminus SPX domain and the C-terminus EXS is a common architecture also found in plant phosphate exporters and in the human phosphate exporter, Xpr1 (see below and Glossary) [16]. Therefore, the uncharacterised yeast Syg1 protein is likely to be also a phosphate exporter.…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 92%
“…(Figure 1), originally identified as the Xenotropic and Polytropic Retrovirus Receptor 1, which is localised on the surface of many cell types [30]. While an initial overexpression study suggested that the SPX domain is not required for Xpr1's phosphate export function [16], a recent human genetic study revealed that several mutations localised within the SPX domain of Xpr1 are responsible for primary familial brain calcification (PFBC), a disease characterized by calcium phosphate deposits in the basal ganglia [33,34]. Biochemical analysis of SPX-mutated Xpr1 proteins revealed that these mutations do reduce phosphate export, demonstrating a regulatory role for the SPX domain in controlling phosphate efflux activity.…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…However, to make this postulation clearer, further studies concerning the shifts of Pi concentration in the PAS and its effect on the PT genes in the two partners are still necessary. In addition, like the PHO1 and XPR1 acting as Pi exporters in plant and animal ( Hamburger et al, 2002 andGiovannini et al, 2013), respectively, the orthologous AM fungal transporters (see Table 1 and Supplemental Figure 20B) responsible for the efflux of Pi to the apoplast also need to be characterized to fully elucidate the regulatory mechanisms of Pi transport at the arbuscule-PAS interface.…”
Section: Gigmpt Belongs To the High-affinity Transporter Family And Mmentioning
confidence: 99%